Performance analysis of spring wheat genotypes under rain-fed conditions in warm humid environment of Nepal - Puri, Ramesh Raj; Gautam, Nutan Raj (International Journal of Environment, 2015)
Around 25% of total wheat area in Terai of Nepal falls under rain-fed and partially irrigated condition. A Coordinated varietal trial (CVT) was conducted during two consecutive crop cycles (2011-12 and 2012-13) under timely sown rain-fed conditions of Terai. The trial was conducted in Alpha Lattice design with two replications at Nepal Agricultural Research Council, National Wheat Research Program, Bhairahawa and Nepal Agricultural Research Council, Regional Agriculture Research Station, Nepalgunj. Observations were recorded for yield and yield traits and analyzed using statistical software Cropstat 7.2.The combined analysis of coordinated varietal trial showed that BL 3978 possessed the highest yield (2469.2 Kg ha-1) followed by NL 1097 (2373.2 Kg ha-1) and NL 1094 (2334.06 Kg ha-1). Genotype x Environment interaction for grain yield was significant (p<0.05) over locations and years. BL 3978 with early maturity (111 days) escaped the heat stress environment. Among the top three genotypes, BL 3978 was consistently higher in both favorable and unfavorable conditions. Earliness was one of the major traits for heat tolerant genotypes. The three identified genotypes will be further evaluated in participatory varietal selection or coordinated farmers field trial followed by small plot seed multiplication (seed increase) and release in the future for timely sown rain-fed conditions. These lines also appear suitable for inclusion in crossing program targeted for water stress tolerance variety development. DOI: http://dx.doi.org/10.3126/ije.v4i2.12649 International Journal of Environment Vol.4(2) 2015: 289-295